Education and Inclusive Growth in West Africa (2021)
Purpose - Many West African countries face the challenge of growth inclusiveness. The region is also facing challenges of equipping its teeming population with high-quality skills despite many reforms and initiatives introduced in the past. This study, thus, identifies education as a crucial contributory factor to growth inclusiveness in the region. It, therefore, examined the role of education in growth inclusiveness in West Africa between 1990 and 2017. Design/methodology/approach - The study utilised different proxies to capture quantity and quality dimensions of education. The unit root and ARDL ""Bounds"" tests were employed at a preliminary stage. Based on the preliminary tests, the study explored autoregressive distributed lags modelling technique to capture the short-run and long-run dynamic effects. Findings - The empirical results reveal a positive impact of school enrolment measures in most of the countries in both short-run and long-run. Education quality measure exerts positive impact and significant in few countries under consideration. Practical implications - These countries should give adequate attention to quality when designing education policy to foster their inclusive growth. Originality/value - This study highlights the critical role of education in the inclusive growth pursuit. Education quantity is important to growth inclusiveness but the quality of education is more fundamental. The quality of education possessed determine to a large extent, what individual can contribute to the productive activities within the economy and accessibility to benefits from economic prosperity."